Meaning of Childbirth Experiences Handled by Traditional Midwives for Mothers in Parung District, Bogor: A Phenomenological Approach in Public Health Studies - Alhikma, Alhikma (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to explore the meaning of childbirth experiences among mothers who delivered with the assistance of traditional birth attendants in Parung District, Bogor.]Methodology: A qualitative study with a descriptive phenomenological approach was conducted. Participants were selected using purposive sampling, consisting of eight mothers who had experienced childbirth assisted by traditional birth attendants. Data were collected through in-depth semi-structured interviews and analyzed using phenomenological thematic analysis to identify significant statements, meaning units, and emerging themes.]Main Findings: The findings identified four major themes shaping mothers’ childbirth experiences: emotional comfort and trust in traditional birth attendants, accessibility barriers to formal health services, influence of family and cultural traditions, and perceptions of safety during childbirth. Although traditional birth attendants provided emotional support and cultural familiarity, concerns regarding medical safety and emergency management were also reported by several participants.Novelty/Originality of this study: This study provides a phenomenological perspective on the lived experiences of mothers delivering with traditional birth attendants in a community where formal maternal health services are available. The research highlights the sociocultural and experiential factors that sustain traditional childbirth practices and offers insights for developing culturally responsive maternal health interventions.]